Two rapidly evolving genes contribute to male fitness in Drosophila. - Reinhardt, J.A.; Jones, C.D. (Journal of Molecular Evolution, 2013)
Purifying selection often results in conservation of gene sequence and function. The most functionally conserved genes are also thought to be among the most biologically essential. These observations have led to the use of sequence conservation as a proxy for functional conservation. Here we describe two genes that are exceptions to this pattern. We show that lack of sequence conservation among orthologs of CG15460 and CG15323-herein named jean-baptiste (jb) and karr, respectively-does not necessarily predict lack of functional conservation. These two Drosophila melanogaster genes are among the most rapidly evolving protein-coding genes in this species, being nearly as diverged from their D. yakuba orthologs as random sequences are. jb and karr are both expressed at an elevated level in larval males and adult testes, but they are not accessory gland proteins and their loss does not affect male fertility. Instead, knockdown of these genes in D. melanogaster via RNA interference caused male-biased viability defects. These viability effects occur prior to the third instar for jb and during late pupation for karr. We show that putative orthologs to jb and karr are also expressed strongly in the testes of other Drosophila species and have similar gene structure across species despite low levels of sequence conservation. While standard molecular evolution tests could not reject neutrality, other data hint at a role for natural selection. Together these data provide a clear case where a lack of sequence conservation does not imply a lack of conservation of expression or function.